Bioecology and management of spiralling whitefly Aleurodicus disperus Russell (Homoptera : Aleyrodidae) - Rani J (Department of Agricultural Entomology, College of Agriculture, 2004)
A study on bioecology and management of spiralling whitefly, Aleurodicus dispersus Russell was carried out in laboratory and pot culture experiments at the Department of Entomology, College of Agriculture, Vellayani, Thiruvananthapuaram during the period 2003-2004. The survey conducted in the instructional Farm, College of Agriculture, Vellayani for a period of one year revealed that Aleurodicus dispersus attacked 50 host plants belonging to 30 families. Averrhoea bilimbi L, Capsicum chinense Jacq., Vigna unguiculata (L.) Walp. Vitis vinifera Linn, Passiflora edulis L., Jacquemontia violaceae Choisy, Spathoglottis aurea Lindle, Ixora chinensis Lam, Alysicarpus vaginalis (L.) DC Chromolaena odorata (L) King and Robinson, and Phaseolus sp, were reported for the first time in India as host plants of spiralling whitefly in the present study. Biology of A. dispersus on cassava, tomato and chilli revealed that cassava was the most susceptible host plant with shorter developmental period and longer adult period and higher fecundity. The eggs were laid on the under surface of leaves in characteristic spiral manner. Eggs were stalked, elliptical and light yellow to tan coloured. There were three nymphal instars and a pupal stage. Adult resembled tiny moths. The wings were clear first, later covered with a waxy powder. The nymphs and adults caused damage to the plants by sucking cell sap from the tender parts of the plants. They excrete honey dew which served as the substrate for the development of sooty mould. Heavy infestation of A dispersus combined with sooty mould infection resulted in loss of plant vigour, unsightly appearance and reduction in yield. The predators reported during the survey were Allograpta javana Wiedemann (Syrphidae; Diptera ), Axinoscymnus puttarudriahi Kapur and Munshi (Coccinellidae; Coleoptera), Cybocephalus indicus Tian and Ramani (Nitidulidae; Coleoptera) and spiders. Two doses each of the formulation viz., Neemazal, Econeem, and plant extract of Andrographis paniculata and Hyptis suaveolens were evaluated with Dimethoate 0.05 per cent as check against A. dispersus on tomato. Three sprayings were given at 45, 60 and 75 days after transplanting. Among the formulated neem products, Neemazal 4 ml 1-1 recorded highest population reduction of eggs, nymphs and adults of A. dispersus on tomato. The neem products were of only moderate efficiency in reducing various life stages of the pest compared to Dimethoate. However, the products can be included in the integrated management of this whitefly, considering the lower toxicity to the natural enemies and environmental safety. Based on the results of the present study, destruction of weed host plants and use of neem products can be suggested for the management of A. dispersus, as an adhoc recommendation.